1999
DOI: 10.1590/s1516-31801999000400003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective assessment of the risk of postoperative pulmonary complications in patients submitted to upper abdominal surgery

Abstract: Objective: To investigate associations between preoperative variables and postoperative pulmonary complications (PPC) in elective upper abdominal surgery. Design: Prospective clinical trial. Setting: A tertiary university hospital. Patients: 408 patients were prospectively analyzed during the preoperative period and followed up postoperatively for pulmonary complications. Measurements: Patient characteristics, with clinical and physical evaluation, related diseases, smoking habits, and duration of surgery. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
4
21

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(103 citation statements)
references
References 31 publications
6
72
4
21
Order By: Relevance
“…Other studies have reported that extubation failure increases the risk of pulmonary complications, mortality, duration of MV, and an increased length of ICU stay (5,6,17). The need for reintubation is a risk factor for the development of pulmonary infection (5,18,19) because it favors bronchoaspiration and alterations in mucociliary clearance, which may lead to bacterial contamination and colonization of the airways (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that extubation failure increases the risk of pulmonary complications, mortality, duration of MV, and an increased length of ICU stay (5,6,17). The need for reintubation is a risk factor for the development of pulmonary infection (5,18,19) because it favors bronchoaspiration and alterations in mucociliary clearance, which may lead to bacterial contamination and colonization of the airways (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was classified by the quantity of cigarettes smoked and the patients were divided into three groups; smokers, ex-smokers and nonsmokers [1]. The nutritional state was evaluated using the Body Mass Index (BMI).…”
Section: Methodsmentioning
confidence: 99%
“…The weight (Kg) was checked using a digital balance (FILIZOLA ® ) and the height was obtained using a anthropometer (cm). We considered the patients to be eutrophic when their BMIs were between 21 and 25 kg/ cm 2 and dystrophic with BMIs of less than 21 or more than 25 kg/cm 2 [1]. The presence of comorbidities was also checked.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations